Hard ticks (Acari: Ixodidae) associated with birds in Europe: Review of literature data - Keve, Gergő; Sándor, Attila D.; Hornok, Sándor (Frontiers in Veterinary Science, 2022)
Hard ticks (Acari: Ixodidae) are considered the most important transmitters of pathogens in the temperate zone that covers most of Europe. In the era of climate change tick-borne diseases are predicted to undergo geographical range expansion toward the north through regions that are connected to southern areas of the continent by bird migration. This alone would justify the importance of synthesized knowledge on the association of tick species with avian hosts, yet birds also represent the most taxonomically and ecologically diverse part of urban vertebrate fauna. Birds frequently occur in gardens and near animal keeping facilities, thus playing a significant role in the dispersal of ticks and tick-borne pathogens in synanthropic environments. The primary aim of this review is to provide a comprehensive reference source (baseline data) for future studies, particularly in the context of discovering new tick-host associations after comparison with already published data. The records on the ixodid tick infestations of birds were assessed from nearly 200 papers published since 1952. In this period, 37 hard tick species were reported from 16 orders of avian hosts in Europe. Here we compile a list of these tick species, followed by the English and Latin name of all reported infested bird species, as well as the tick developmental stage and country of origin whenever this information was available. These data allowed a first-hand analysis of general trends regarding how and at which developmental stage of ticks tend to infest avian hosts. Five tick species that were frequently reported from birds and show a broad geographical distribution in the Western Palearctic (Ixodes arboricola, I. frontalis, I. ricinus, Haemaphysalis concinna and Hyalomma marginatum) were also selected for statistical comparisons. Differences were demonstrated between these tick species regarding their association with bird species that typically feed from the ground and those that rarely occur at the soil level. The ecology of these five bird-infesting tick species is also illustrated here according to avian orders, taking into account the ecology (habitat type) and activity (circadian rhythm and feeding level) of most bird species that represent a certain order.